Family support on intensive care units during the COVID-19 pandemic: a qualitative evaluation study into experiences of relatives - Hanna T. Klop; Mana Nasori; Tjitske W. Klinge; Rianne Hoopman; Mirjam A. de Vos; Chantal du Perron; Lia van Zuylen; Monique Steegers; Birkitt L. ten Tusscher; Floor C. H. Abbink; Bregje D. Onwuteaka-Philipsen; H. Roeline W. Pasman (BMC, 2021)
Abstract Background During the first peak of the COVID-19 pandemic in the Netherlands, relatives of patients with COVID-19 admitted to Intensive Care Units (ICUs) were severely restricted in visiting their relatives and in communicating with treating physicians. Family communication is a core element of critical care, however, this pandemic forced medical ICU staff to arrange alternative family support for instance by Family Support Teams (FSTs), consisting of non-ICU affiliated staff who telephonically contacted relatives. This study aims to examine relatives' experiences with FSTs on two ICUs of a Dutch university medical centre, and to evaluate its working strategies. . Methods In a semi-structured interview study, relatives of patients with COVID-19 admitted to ICU's, who had been supported by the FSTs, were sampled purposively. Twenty-one interviews were conducted telephonically by three researchers. All interviews were topic list guided and audio-recorded. Data was analysed thematically. Results All participants indicated they went through a rough time. Almost all evaluated the FSTs positively. Four major themes were identified. First, three important pillars of the FSTs were providing relatives with transparency about the patients' situation, providing attention to relatives' well-being, and providing predictability and certainty by calling on a daily basis in a period characterised by insecurity. Second, relatives appeared to fulfil their information needs by calls of the FSTs, but also by calling the attending ICU nurse. Information provided by the FSTs was associated with details and reliability, information provided by nurses was associated with the patient's daily care. Third, being a primary family contact was generally experienced as both valuable and as an emotional burden. Last, participants missed proper aftercare. Family support often stopped directly after the patient died or had left the ICU. Relatives expressed a need for extended support after that moment since they had strong emotions after discharge or death of the patient. Conclusions Family support in times of the extreme COVID-19 situation is important, as relatives are restricted in communication and have a strong need for information and support. Relatives feel encouraged by structure, frequency, support and understanding by FSTs. However, remote family support should be tailored to the needs of relatives. A fixed contact person on de ICU and video calling might be good extra options for family support, also in future post COVID-19 care, but cannot replace physical visits.